Modular Design for a Flexible IoT Monitoring and Control Application using Flutter - Putra, Fajri Profesio; Subandri, Muhammad Asep (Politeknik Negeri Bengkalis, 2024)
The Internet of Things (IoT) has emerged as a transformative technology that enables smart environmentsthrough extensive sensor networks and connected devices. However, the diversity and heterogeneity of IoT devices posesignificant challenges in developing versatile applications capable of monitoring and controlling a broad spectrum ofsensors and actuators. This paper proposes a novel modular design for a flexible IoT monitoring and control applicationusing Flutter, a popular framework for developing cross-platform solutions. Our design leverages Flutter’s robust UIcapabilities and its efficient communication with backend services to offer a scalable and customizable interface that canadapt to various IoT deployments, from domestic to industrial settings. The modular architecture allows users to specifyand configure the application to dynamically include any combination of devices and functionalities, catering to specificneeds without additional programming